2009
DOI: 10.1080/03009740902922612
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated skin lesions in patients treated with anti-tumour necrosis factor alpha inhibitors

Abstract: Our results on patients treated with TNF antagonists strongly support a link between TNF inhibition and IMSL development. Although these clinical complications are rare, clinicians should be aware of their occurrence and should recognize them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 13 publications
0
71
0
4
Order By: Relevance
“…We additionally observed a relative decrease in production of TNF-α in subjects carrying the high-risk MHC class II haplotype. The role of TNF-α in the pathogenesis of vitiligo is less clear (30)(31)(32)(33); in the skin of vitiligo patients, TNF-α is produced by perilesional T cells and is involved in the development of cytotoxic T lymphocytes (34). However, treatment with TNF-α blocking agents, such as adalimumab and infliximab, can be paradoxically associated with de novo vitiligo development in patients with other autoimmune conditions (30)(31)(32)(33)35).…”
Section: Discussionmentioning
confidence: 99%
“…We additionally observed a relative decrease in production of TNF-α in subjects carrying the high-risk MHC class II haplotype. The role of TNF-α in the pathogenesis of vitiligo is less clear (30)(31)(32)(33); in the skin of vitiligo patients, TNF-α is produced by perilesional T cells and is involved in the development of cytotoxic T lymphocytes (34). However, treatment with TNF-α blocking agents, such as adalimumab and infliximab, can be paradoxically associated with de novo vitiligo development in patients with other autoimmune conditions (30)(31)(32)(33)35).…”
Section: Discussionmentioning
confidence: 99%
“…tempered skin inflammation with lymphocytes leaving the skin (15-17); impaired adhesion molecule expression [e.g. CLA-counterligand E-selectin) on skin microvasculature (18,19); relapsing patients: IFN-alphamediated disease relapse with skin-infiltrating lymphocytes (20)(21)(22)(23), provoking role of underlying infections (24)(25)(26)(27)(28)]. We recommend further investigations to find clear elucidation for our observations and confirm our primary results establishing a potential role of CLA in predicting long-term effectiveness of TNFalpha inhibitor therapy in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Not only have studies shown this not to be the case [15], alopecia areata has actually been found to occur during treatment with TNF-α inhibitors. The first case was reported in 2004 with the use of infliximab [16] and since then we have identified 34 cases in the literature, including the TNF-α inhibitors adalimumab [4,[17][18][19][20][21][22][23][24][25][26][27], infliximab [16,23,[28][29][30][31][32], and etanercept (Table 1) [4,22,33,34]. In these cases, alopecia areata was diagnosed by both clinical presentation and histopathology, which was available in the majority of cases.…”
Section: Clinical Subtypes Of Alopecia Seen During Treatment With Tnfmentioning
confidence: 99%